Leading libraries : how to create a service culture - VanDuinkerken, Wyoma; Kaspar, Wendi Arant (Chicago : ALA Editions, an imprint of the American Library Association, 2015)
The authors explore the act of leading in libraries, with a focus on the acts and behaviors that manifest. They also explore how such actions are derived from individual interactions with others, and how they impact a larger organization. Consideration is given to the value of strategic planning, and the importance of formalizing service leadership in processes and policies.
Leadership theories : traditional and transformational -- Service leadership and its paradigm in libraries -- Conscientiousness as the foundation -- Building rapport -- Balancing encouragement and accountability -- Innovation and evolving service -- Strategic planning : the practice of innovation and strategic thinking -- Sustaining service as a value -- Formalizing service leadership in libraries : embedding processes and policies -- Service leadership in libraries.
Includes bibliographical references (pages 153-161) and index.
Keywords: Public services (Libraries); Library personnel management; Leadership; Customer relations